A Trade-Off between Mechanical Strength and Erosive Wear Resistance in AlSi12CuMgNi Alloy Used to Manufacture Fan Blades for Underground Mines - Florentino Alvarez-Antolin; Elvira Segurado-Frutos; Alejandro González-Pociño; Alberto Cofiño-Villar; Juan Asensio-Lozano (Metals, 2019)
The axial fan blades used in underground mines are usually manufactured in AlSi12CuMgNi alloy (EN AC 48000). They must have a high mechanical strength to withstand the stresses resulting from the rotation speed of the rotor and a high resistance to erosive wear caused by suspended particles from underground mining and transport operations. The aim of this paper is to determine the most suitable thermal treatment to simultaneously improve their mechanical strength and erosive wear resistance. To this end, two solution treatments at 525 °C with cooling in water were analysed, as well as several ageing times at 170 °C. The crystalline phases present in the as-cast state were quantified by X-ray diffraction following quenching and different ageing processes. Furthermore, erosion wear resistance was measured by means of compressed air blasting with corundum particles according to ASTM G76 (2004). The highest wear resistance was obtained in the as-cast state using gravity die casting, with the presence of Al4Cu2Mg8Si7 and Al3CuNi. This wear resistance was higher than that obtained after the ageing treatment. However, a trade-off between mechanical strength and wear resistance was observed after 12 h ageing, where the hardness obtained exceeded 160 HV and the wear resistance became similar to that obtained in the as-cast state.